Class and Civil Society : the Limits of marxian Critical Theory - COHEN, Jean L. (The University of Massachusetts Press, 1982)
Marxian class theory has been unable to account for the most significant historical developments of the 20th century. The rise of fascism not only belied the hopes put in the revolutionary proletariat, it also brought into the center of the political stage those social strata which the class theory had relegated to, at best, secondary supporting roles. The triumph of the Bolshevik, revolution and the institutionalization and expansion of Soviet socialism has not only failed to issue into the anticipated free, classless society, but has led to the creation of a new system of stratification and domination which is simply unthinkable within the classical Marxian framework. Late or advanced capitalism continues advancing in spite of all its crises and contradictions.